Katerina's wish - Mobley, Jeannie (Margaret K. McElderry Books, 2012)
Thirteen-year-old Trina's family left Bohemia for a Colorado coal town to earn money to buy a farm, but by 1901 she doubts that either hard work or hoping will be enough, even after a strange fish seems to grant her sisters' wishes.